2010
DOI: 10.1007/s12126-010-9063-2
|View full text |Cite
|
Sign up to set email alerts
|

Criminological Theory and Elder Abuse Research—Fruitful Relationship or Worlds Apart?

Abstract: By definition, elder abuse research touches upon topics also covered by criminological theories. However, up until now, attempts to apply criminological theories to this field of research are scarce and the potential of criminological theory to enhance the understanding of elder abuse phenomena appears underdeveloped. The paper explores potentials and limitations of applying both theories and their related concepts from criminology to elder abuse. Financial elder abuse and abuse and neglect in domestic caregiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 58 publications
0
28
0
Order By: Relevance
“…As such, understandings about elder abuse are considered to be shaped by bio-social-cultural-political-historic factors and notions about the nature of elder abuse are likely to be multiple and varied, and practice complex and uncertain. This is evidenced in the literature where opinions about what constitutes elder abuse have been debated for a number of decades (Penhale & Parker, 2008;Göergen & Beaulieu, 2010;Anand, Begley, O'Brien, Taylor & Killick, 2013;Phelan, 2014) and where it is observed that social workers navigate this complexity and uncertainty by developing their own particular ways of working (Estes, Biggs & Phillipson, 2003).…”
Section: Research Aims and Questionmentioning
confidence: 99%
See 4 more Smart Citations
“…As such, understandings about elder abuse are considered to be shaped by bio-social-cultural-political-historic factors and notions about the nature of elder abuse are likely to be multiple and varied, and practice complex and uncertain. This is evidenced in the literature where opinions about what constitutes elder abuse have been debated for a number of decades (Penhale & Parker, 2008;Göergen & Beaulieu, 2010;Anand, Begley, O'Brien, Taylor & Killick, 2013;Phelan, 2014) and where it is observed that social workers navigate this complexity and uncertainty by developing their own particular ways of working (Estes, Biggs & Phillipson, 2003).…”
Section: Research Aims and Questionmentioning
confidence: 99%
“…International literature pinpoints similar factors for abuse in later life (Nerenberg, 2008;McClennen, 2010;Göergen & Beaulieu, 2010;Payne, 2011). However, it is important to recognise that these factors could equally apply to abuse in whānau/families more generally.…”
Section: Risk Indicatorsmentioning
confidence: 99%
See 3 more Smart Citations